2019
DOI: 10.1186/s43088-019-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of cinnamaldehyde and costunolide to counteract metabolic syndrome induced by excessive fructose consumption

Abstract: Background: One of the serious public health problems in the world is metabolic syndrome. It includes visceral obesity, dyslipidemia, insulin resistance, hyperglycemia, and hypertension. As a contributor to almost all the classic signs of metabolic syndrome, fructose was the ideal choice. There are certain shortcomings with existing drugs for insulin-resistant treatment. Plants still represent the main source of most available medicines. Cinnamaldehyde (CNA) is an active principle of Cinnamomum zeylanicum. Cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Cinnamaldehyde in the form of cinnamon powder has also been shown to reduce glucose, total cholesterol, triglycerides, and LDL cholesterol levels in T2DM patients ( 70 ). Furthermore, cinnamaldehyde treatment reduced the serum levels of triglycerides, total cholesterol, c-LDL and elevated the c-HDL levels in high-fat diet rats ( 71 ). This evidence suggests the involvement of TRPA1 in lipid homeostasis.…”
Section: Trpa1 Channels In Metabolic Disordersmentioning
confidence: 99%
“…Cinnamaldehyde in the form of cinnamon powder has also been shown to reduce glucose, total cholesterol, triglycerides, and LDL cholesterol levels in T2DM patients ( 70 ). Furthermore, cinnamaldehyde treatment reduced the serum levels of triglycerides, total cholesterol, c-LDL and elevated the c-HDL levels in high-fat diet rats ( 71 ). This evidence suggests the involvement of TRPA1 in lipid homeostasis.…”
Section: Trpa1 Channels In Metabolic Disordersmentioning
confidence: 99%
“…Cin treatment on the other hand, reduced the toxic effect of TeA as evidenced in the present study. Earlier studies on the ameliorative effect of Cin have shown reduced body weight in obese male mice and rats that were fed a high-fat diet ( Zuo et al, 2017 ; Rashwan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metformin's augmentation of the lipid profile is due to the activation of AMPK in hepatic cells; as a result, Acetyl-CoA carboxylase (ACC) activity is lowered. [55].…”
Section: Discussionmentioning
confidence: 99%